Positive parenting for healthy living (Triple P) for parents of children with type 1 diabetes: protocol of a randomised controlled trial. Issue 1 (December 2016) - Lohan, Aditi; Mitchell, Amy; Filus, Ania; Sofronoff, Kate; Morawska, Alina
Abstract Background Type 1 diabetes is a serious, life-long condition which causes major health, social and economic burden for children, their families and the community. Diabetes management involves strict adherence to a complex regimen, and poor management and non-adherence are a persistent problem among children. Parent-child interactions and parenting have been identified as crucial points of intervention to support children's health and emotional well-being, yet few parenting interventions have been developed or evaluated for parents of young children. This paper describes a randomised controlled trial of a brief, group-based parenting intervention for parents of young children (2-10 years) with type 1 diabetes compared against care as usual (CAU). Methods/design Families will be randomised to either Positive Parenting for Healthy Living Triple P or CAU. Positive Parenting for Healthy Living Triple P involves 2 × 2 h group sessions. Outcomes will be assessed via parent and child questionnaire, home observations and blood glucose monitoring at baseline, 1-month and 6-months post-intervention. Primary outcomes will be parent- and child-reported parenting behaviour, parent-reported child behaviour and adjustment, and parent-reported child quality-of-life. Secondary outcomes will include parental self-efficacy with diabetes management, illness-specific and general parenting stress, parent-reported child illness behaviour, family quality-of-life, observed parenting and child behaviour, and child's illness control. Discussion The theoretical background, study hypotheses, methods and planned analyses are discussed. Trial registration Australian New Zealand Clinical Trials Registry:ACTRN12613001281785 . Registered 20 November, 2013.